PENGARUH GAYA KEPEMIMPINAN DAN KEMAMPUAN PEGAWAI TERHADAP KINERJA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI JAWA TENGAH DALAM MENYELESAIKAN LAPORAN PENGADUAN MASYARAKAT - Nur Dila Alfi Isnindya; Tri Yuniningsih (Journal of Public Policy and Management Review, 2018)
The Ombudsman of Republic of Indonesia (RI) is a state institution that serves to oversee the public services to ensure that people obtain excellent service. The Ombudsman of RI has a representation in each province. One of them is the Ombudsman of RI Central Java Province Representative. The performance of Ombudsman of Central Java Province Representative in completing the report is still not optimal because it has not yet reached the target completion of the report. This research uses quantitative approach. The samples are 12 respondents who are employees of Ombudsman of RI Central Java Province Representative. This research uses quota sampling. The analysis which is used is Rank Spearman correlation test and coefficient of determination. The result indicates that the performance of Ombudsman of RI Central Java Province Representative is good although it is not reached the specified target yet. The result of the hypothesis test shows that there is positive correlation but no significant between leadership style and performance of Central Java Province Representative. This is proved by sig (2 tailed)> α = 0,05 which is 0,068> 0,05 with the influence percentage of 29,4849%. Moreover, there is positive relationship but no significant between the ability of employees with the performance of Ombudsman RI Representative of Central Java Province as evidenced by the number sig (2 tailed)> α = 0.05 which is 0.890> 0.05 with the influence percentage of 0.2025%. Suggestions related to this study is the addition of assistants adjusted with the needs of each representative, providing training equally for assistants who have the same level, and providing advanced training and foreign language training to improve the competence of the assistant.